IoT Based Household Elderly Monitoring System with Connection Through Wi-Fi - Choong, Wei Jun; Saparudin, Faiz Asraf (Progress in Engineering Application and Technology, 2025)
Malaysia’s aging population has led to an increased risk of elderly individuals living alone experiencing falls and delayed medical attention, compounded by the limitations of current solutions such as privacy concerns, high costs, and complex installation. To address these issues, this project introduces a cost-effective and user-friendly IoT-based surveillance system designed specifically for visually impaired elderly individuals. By utilizing ESP32-CAM, ESP32, and ESP32-C3 devices integrated into a wearable solution, the system transmits live image and ambient environmental data to enable early detection of distress signals, focusing on low latency, speed, and accuracy to ensure timely assistance. Experimental results show that the system significantly reduces response times compared to traditional phone-based methods by 69.5% while prioritizing user privacy and data security through secure transmission and access controls, offering a promising solution to enhance the safety and well-being of elderly individuals living independently.